Predictive value of complete blood count parameters for placental invasion anomalies. (2nd October 2017) - Abide Yayla, Cigdem; Ozkaya, Enis; Tayyar, Ahter; Senol, Taylan; Senturk, M. Baki; Karateke, Ates
Abstract: Background : The aim of this study was to assess the relationship between some complete blood count parameters and placental invasion anomalies. Methods : Totally 146 pregnancies who were suspected for placental invasion anomalies underwent complete blood count screening before cesarean section. In all subjects white blood cell, lymphocyte, neutrophil and platelet counts with red cell distribution width (RDW), mean platelet volume (MPV), hemoglobin and hematocrit levels were analyzed. All complete blood count parameters were analyzed to predict placental invasion anomalies. Results : Among 146 pregnancies histopathologically confirmed placental invasion anomaly was diagnosed in 46 cases. There were significant differences between groups with and without placental invasion anomaly in terms of age, neutrophil, platelet count, MPV, RDW and neutrophil to lymphocyte ratio ( p  < 0.05). Age (AUC = 0.719, p  < 0.001), neutrophil to lymphocyte ratio (AUC = 0.639, p = 0.008) and MPV (AUC = 0.807, p  < 0.001) were significant predictors for the cases with placental invasion anomaly. In multivariate analyzes age, MPV, RDW and neutrophil to lymphocyte ratio were significantly associated with the placental invasion anomaly. Conclusion : In addition to the sonographic findings, simple blood count parameters may be utilized to confirm cases with suspected for placental invasion anomalies.